Comparison of the efficacy of dexmedetomidine with that of esmolol in attenuating laryngoscopic and intubation response after rapid sequence induction - Yallapragada, Srivishnu Vardhan (Anesth Essays Res, 2014)
CONTEXT: Laryngoscopy and tracheal intubation produce sympathetic overdrive by catecholamine release resulting in hypertension and tachycardia. Various agents are being tried to combat the intubation response over years. AIMS: This study is aimed at comparing dexmedetomidine which is a highly selective alpha-2 agonist with an ultra-short acting beta blocker, esmolol to see which among the two is better in attenuating the hemodynamic response to laryngoscopy and tracheal intubation. SETTINGS AND DESIGN: This was a prospective randomized double-blind control study. SUBJECTS AND METHODS: Sixty patients scheduled for general anesthesia were divided into two groups, D and E with 30 patients in each group. Group-D patients received dexmedetomidine 0.5 mcg/kg and Group-E patients received esmolol 0.5 mg/kg as intravenous premedication over 5 min before a rapid sequence induction and tracheal intubation. Systolic, diastolic and mean arterial pressures along with heart rate were measured using invasive arterial line at various time points. The percentage change of hemodynamic parameters at those time points from the baseline was compared between the groups. STATISTICAL ANALYSIS USED: Descriptive and inferential statistical methods were used to analyze the data. RESULTS: The percentage change of all hemodynamic parameters from base line were less in the dexmedetomidine group than in esmolol group at all-time points of measurement. However, a statistically significant difference was observed often at the time points within 1 min after tracheal intubation. CONCLUSIONS: Dexmedetomidine is superior to esmolol in attenuating the hemodynamic response to laryngoscopy and tracheal intubation.